Effect of Graphene Quantum Dots (GQDs) on the Mechanical Properties of Fiber-Reinforced Concrete - Suksumran, Korakot; Kunawisarut, Atichon; Jongvivatsakul, Pitcha (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
This study aims to explore the impact of incorporating graphene quantum dots (GQDs) into fiber-reinforced concrete (FRC) to enhance its mechanical performance. In the experiment, FRC mixtures were prepared with polypropylene (PP) fiber contents of 0.5% and 1.5% by volume, while a fixed dosage of 0.3% GQDs by cement weight was added to assess their influence. A total of 30 specimens, consisting of cylindrical and beam-shaped samples, were prepared and cured for 28 days. Compressive and flexural tests were performed to evaluate critical mechanical properties, including compressive strength, elastic modulus, flexural strength, and flexural toughness. The findings provide insights into the combined effects of GQDs and PP fibers on enhancing the mechanical performance of FRC, offering potential for advanced construction materials.